Programação de produção levando em conta máquinas em paralelo e set-up dependente da sequência de produção - Luiz, Rodrigo Marcus Dias Luiz (2012)
Due to economic growth, companies in general – but particularly manufacturing industries - end up looking for a way to eliminate losses that are evident and others that are not so easy to identify so as to maximize profits. This project seeks for an optimal production schedule to increase the availability of a device responsible for manufacturing more than one product. With increased demands from customers, industry is compelled to vary its production mix so that it can not have equipment dedicated to each produced model type. Thus, the use of operational research approaches is more and more required to be able to set up a production schedule in a faster and assertive way. One can not stop considering the influence of equipment availability for a smoother production scheduling. Aligned with this, when evaluating the major losses at the equipment, there is a need to reduce the set-up time. To make this possible, it is suggested the implementation of the SMED methodology, which was created within Lean Manufacturing - more specifically, by TPM system. From the perspective of optimization, the proposed problem is challenging since there are multiple identical parallel processors with sequence dependent set-ups. Thus, it is up to the proposed system to define how much of the total demand for each product will be produced in each of the processors in order to minimize the total set-up time. In other words, production lots have no fixed size. It was proposed a hybrid approach using dispatch rules (heuristics) for the solution of the proposed problem that have presented satisfactory results.